Multi-goal optimization of a carry-mould - REGGIANI, B.; COSMI, F. (Engineering Transactions, 2009)
A common engineering task is the optimization of components that are part of multibody assemblies, in which it is difficult to extrapolate and define the boundary conditions to be applied for the component optimization. This work presents a procedure for multi-goal optimization of components that are integrated in multipart engineering systems. The efficiency of the procedure is illustrated by means of a test case, a carry-mould that is part of a multicomponent blowing machinery. Target goals of the optimization process are the minimization of moment of inertia and of global mass and the maximum allowable displacement in a number of control points.